Amusement Parks : Perimeter and Area - Irving, Dianne; Johson, Sara (Huntington Beach, CA : Teacher Created Materials, 2011)
Explore amusement parks and some of the most thrilling roller coasters around the world while discovering concepts of perimeter and area. Amusement Parks explains how measuring perimeter and area helps in the planning and construction of amusement parks and helps to ensure fun and safety for guests.
Includes index and answer key
Keywords: Amusement parks -- Design and contructions -- Juvenile literature; Perimeter (Geometry) -- Juvenile literature; Area measurement -- Juvenile literature